Women As ‘Other’ In The Drama The Trifles By Susan Glaspel (PANOPTICON: Journal of English Studies, 2024)
This study discusses a matter of women discrimination faced by women character in the drama The Trifles by Susan Glaspell. As a feminist, Glaspell shows in her one-act drama that women are often depicted as individual who are less than men. Women is often being dismissed and have second place in society. This study is aimed to see how women is portrayed as the Other by the men in their life. This research is a descriptive qualitative study and using feminist approach. This study used a drama script The Trifles by Susan Glaspell as the main data. Gender theory by Simone de Beauvoir will be used as the main theory of this research. The main data collected after doing a throughout reading the drama script. The result shows that women are considered ‘other’ half by the men and that men decides that women nature is to nurture